A comparison of physical and technical match performance of a team competing in the english championship league and then the english premier league following promotion - Morgans, R.; Adams, D.; Mullen, R.; Sacramento, J.; McLellan, C.; Williams, M.; Gerrard, B.; MacRae, H. (International Journal of Sports Science and Coaching, 2015)
The changes in match demands when a team is promoted from the English Championship League (ECL) to the English Premier League (EPL) remain unknown. To date, estimates of between-league differences are made using different teams. This study explores differences in physical and technical performance of players who competed in the ECL and then the EPL following promotion. Although total distance covered over the season was the only measure to significantly differ ( p = 0.0001) between the ECL and EPL, the 3% increase in total distance in the EPL was deemed practically non-significant. In the EPL, players had an extra 57 ± 6 hours ( p = 0.0002) between matches, yet this had little affect on total, sprint and high intensity distances. In summary, higher league standard may not require greater physical capacity and developing a tactical strategy to suit the ability of players that is sustainable across leagues is important.